Role of Staphyloxanthin in the lateral diffusion coefficient of a Staphylococcus aureus model membrane system (2023)
Lateral diffusion can be understood as the stochastic motion of microscopic molecules in a two-dimensional surface. The associated lateral diffusion coefficient gives the amount of area covered by a particle moving in lateral diffusion in a determined time. In biological sciences, this coefficient gives insights into the molecular dynamics of cells and their interaction with biomolecules such as proteins and enzymes. Furthermore, Staphylococcus aureus (abbreviated as S. aureus ) is one of the most relevant bacteria due to its large incidence of respiratory infections and its resistance to multiple commercial antibiotics. Among S. aureus defense mechanisms, Staphyloxanthin (STX) stands out as a carotenoid molecule capable of stopping oxidation processes in S. aureus membrane in high-stress conditions. In previous literature, the effects of STX in different biophysical properties of S. aureus membrane such as rigidity and elastic bending constant have been characterized; however, the effect of STX in the lateral diffusion coefficient of S. aureus membrane still remains unknown. In this work, we characterize the Fluorescence Correlation Spectroscopy (FCS) technique to measure lateral diffusion coefficients in biological membranes by the autocorrelation function associated to the measured membrane fluorescence signal in a confocal microscope. By using this technique, we successfully measured the lateral diffusion coefficient of giant unilamellar vesicles (GUVs) made of the lipid DOPC along with the lipophillic fluorophore DiI at 37°C and 45◦C, corroborating the effect of temperature in diffusion dynamics. Additionally, we observed the effects of STX (15mol%) in the lateral diffusion coefficient of S. aureus model membrane GUVs made of the lipids DMPC (85mol%), DMPG (15mol%) and DiI. The presence of STX increases the lateral diffusion coefficient by almost 2^2/ when compared to the case without STX at 37°C. These results are expected to expand the knowledge on the biophysical properties of S. aureus and give additional insights into the possible ways to treat S. aureus infections without the use of antibiotics.